A review of computer-aided design/computer-aided manufacture techniques for removable denture fabrication - Bilgin, Mehmet Selim (Eur J Dent, 2016)
The aim of this review was to investigate usage of computer-aided design/computer-aided manufacture (CAD/CAM) such as milling and rapid prototyping (RP) technologies for removable denture fabrication. An electronic search was conducted in the PubMed/MEDLINE, ScienceDirect, Google Scholar, and Web of Science databases. Databases were searched from 1987 to 2014. The search was performed using a variety of keywords including CAD/CAM, complete/partial dentures, RP, rapid manufacturing, digitally designed, milled, computerized, and machined. The identified developments (in chronological order), techniques, advantages, and disadvantages of CAD/CAM and RP for removable denture fabrication are summarized. Using a variety of keywords and aiming to find the topic, 78 publications were initially searched. For the main topic, the abstract of these 78 articles were scanned, and 52 publications were selected for reading in detail. Full-text of these articles was gained and searched in detail. Totally, 40 articles that discussed the techniques, advantages, and disadvantages of CAD/CAM and RP for removable denture fabrication and the articles were incorporated in this review. Totally, 16 of the papers summarized in the table. Following review of all relevant publications, it can be concluded that current innovations and technological developments of CAD/CAM and RP allow the digitally planning and manufacturing of removable dentures from start to finish. As a result according to the literature review CAD/CAM techniques and supportive maxillomandibular relationship transfer devices are growing fast. In the close future, fabricating removable dentures will become medical informatics instead of needing a technical staff and procedures. However the methods have several limitations for now.